2016
DOI: 10.2134/agronj2015.0497
|View full text |Cite
|
Sign up to set email alerts
|

Winter Wheat Cropping System Response to Seed Treatments, Seed Size, and Sowing Density

Abstract: Poor stand establishment resulting in lower yield is a major constraint to expanding winter wheat (Triticum aestivum L.) across western Canada. To address this issue, we conducted a study totaling 26 site‐years over three growing seasons (2011–2013) to observe crop responses to system manipulations involving seeding rate (200 and 400 seeds m−2), seed size as a proxy for plant vigor (light/thin, moderate, heavy/plump), and a dual fungicide/insecticide seed treatment, on crop establishment, yield, and seed quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…In the current study, only certified seed with germination levels of >90%, and little or no infection with F. graminearum was used. In a companion study by Beres et al (2016) the same dual fungicide/ insecticidal seed treatment, as used in the current study, increased winter wheat fall and spring plant density as well as winter survival. They also reported that the same combination seed treatment, increased grain yield and net returns, especially when a lower seeding rate was used (Beres et al, 2016).…”
Section: Treatment Effectsmentioning
confidence: 68%
See 3 more Smart Citations
“…In the current study, only certified seed with germination levels of >90%, and little or no infection with F. graminearum was used. In a companion study by Beres et al (2016) the same dual fungicide/ insecticidal seed treatment, as used in the current study, increased winter wheat fall and spring plant density as well as winter survival. They also reported that the same combination seed treatment, increased grain yield and net returns, especially when a lower seeding rate was used (Beres et al, 2016).…”
Section: Treatment Effectsmentioning
confidence: 68%
“…In a companion study by Beres et al (2016) the same dual fungicide/ insecticidal seed treatment, as used in the current study, increased winter wheat fall and spring plant density as well as winter survival. They also reported that the same combination seed treatment, increased grain yield and net returns, especially when a lower seeding rate was used (Beres et al, 2016). Fall-applied foliar fungicide (prothioconazole) reduced leaf disease severity at GS 83 and improved grain yield, and weakly affected grain protein concentration (P < 0.10), and net returns (Table 5).…”
Section: Treatment Effectsmentioning
confidence: 68%
See 2 more Smart Citations
“…Sowing density and, consequently, crop density is an important factor in determining the competitive ability of cereals against weeds (Doll et al, 1995;Kristensen et al, 2008) as well as the expression of their grain yield potential (Beavers et al, 2008;Beres et al, 2016;Li et al, 2016). The crop density to grain yield relationship is not directly proportional.…”
Section: Introductionmentioning
confidence: 99%